The influence of teachers' content knowledge and pedagogical content knowledge in science when judging students' science work. - Hickey, Ruth L. (Curtin University, 1999)
Primary and secondary teachers in Western Australian have adopted a new Curriculum Framework (Curriculum Council, 1998a) which is outcomes-focused and endorses a constructivist approach to science for school students. This research examines the influence of teachers' science content knowledge on how they make judgements about students' conceptual understandings and the extent to which follow-up activities they suggest reflect a conceptual change approach to teaching science.Primary and secondary teachers, from a range of science education histories and experiences teaching students of different ages, responded to a science task involving concepts of heat energy, combustion and ignition. They were asked to judge a student work sample about the same task, and suggest follow-up activities to support further learning.How teachers made their judgements was found to vary in accord with their science knowledge, categorised as high, midrange and low. Teachers with high science knowledge were the most adept at making accurate and appropriate judgements and had the lowest frequency of problems with their judgements. Teachers with high and midrange science knowledge were more able to link their suggestions for follow-up activities to students' science concepts, and showed greater familiarity with activities commensurate with a conceptual change orientation to teaching. Non-recognition of students' concepts as critical evidence of development was a key aspect of the judgements of teachers with low science knowledge.Recommendations are made for professional development to assist teachers to develop appropriate science content knowledge they can use to support their pedagogical content knowledge so they are able to foster students' conceptual development.